The state of bone metabolism in lung cancer patients - Dumansky, Y.V.; Syniachenko, O.V.; Stepko, Ph.A.; Taktashov, G.S.; Chernyshova, O.Y. (Experimental Oncology, 2018)
In recent years, we have discussed the correlation of malignant tumor process with the development of osteoporosis, which can be exacerbated by ongoing chemotherapy and radiation therapy. The aim of the work was to assess the status of bone metabolism in 32 untreated patients with lung cancer without metastasis. Materials and Methods: Patients underwent dual-energy X-ray osteodensitometry of proximal part of femoral bone. Osteopontin (OP), osteocalcin (OC) and alkaline phosphatase (AP) parameters were studied in blood, as well as osteo-associated chemical elements. Results: Lung cancer proceeds with severe disorders of bone metabolism, which is accompanied by an increase in blood levels of OP, OС, AP, phosphorus, lithium, lead, strontium and cobalt against a decrease of calcium, magnesium and manganese, which were observed in 75; 78; 31; 100; 66; 47; 44; 3; 100; 100, and 6% of patients, respectively; such disorder was associated with a morphological variant of the tumor (cobalt) and stage of disease (calcium, magnesium, manganese, strontium), development of osteodeficit (OP, OC, AR, strontium, zinc). Osteodeficit in the form of osteopenia and osteoporosis is observed more common in women, in every second patient, and osteodensimetric T-score depends on the age of patients, directly correlates with the values of the OP and OC, and inversely — with a zincemia rate. Conclusions: The disorders of bone metabolism in patients with lung cancer indicate the need for the development of antiosteoporosis treatment for cancer patients. Key Words: lung cancer, bone metabolism.